AGRICULTURE IN THE CONTEXT OF NATIONAL RESILIENCE TO IMPROVE THE NATION'S SOCIOECONOMIC - Ernawati; Dicky R Munaf; Rusdiana; Indratmo Soekarno; Syahrul Firdaus Arya Lesmana (UIN Sunan Gunung Djati Bandung, 2026)
National resilience is a strategy to mobilize and optimize all national resources through the management of space, time, and situations to achieve national objectives based on the ideology and constitution of the Unitary State of the Republic of Indonesia. In the concept of national resilience developed by Lemhannas, agriculture occupies a strategic position as a key parameter in the economic aspect of Astagatra. This study aims to analyze the role of the agricultural sector in strengthening national resilience and improving the socioeconomic conditions of the community. This study employs a qualitative descriptive approach through literature review and conceptual analysis by examining the interrelationships between agriculture, food security, economic development, and national resilience. The results of the study indicate that the agricultural sector makes a significant contribution to national development through food provision, labor absorption, foreign exchange earnings, increased income for rural communities, poverty reduction, the supply of industrial raw materials, and the strengthening of linkages among economic sectors. Furthermore, agriculture plays a vital role in maintaining food security, price stability, and inflation control; supporting the development of agroindustry; and driving economic growth. These contributions create a multiplier effect that strengthens economic stability, social welfare, and national competitiveness. Agriculture is viewed not only as a production sector but as a multidimensional strategic system capable of driving the economy, maintaining social stability, supporting industrialization, and underpinning national resilience. Strengthening the agricultural sector through sustainable development, technological innovation, and increased productivity is a key factor in supporting Indonesia’s national resilience and future socioeconomic development.